TPACK, Self-Efficacy, and Teaching Readiness: The Mediating Role of Reflective Practice in Pre-Service Economics Teachers - Maryani, Leni; Ramafrizal, Yudho; Salsabila Syarobti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to investigate the mediating role of reflective practice in the relationships between Technological Pedagogical Content Knowledge (TPACK), self-efficacy, and teaching readiness among pre-service economics teachers in Indonesia. A cross-sectional quantitative survey was conducted with 60 pre-service economics teacher students at FKIP Universitas Pasundan (cohorts 2022–2023) using total sampling. PLS-SEM with 5,000-subsample bootstrapping in SmartPLS 4.0 was employed. TPACK (β = .431, p < .001) and self-efficacy (β = .372, p < .001) significantly predicted reflective practice, which in turn predicted teaching readiness (β = .418, p < .001). TPACK (β = .312, p < .001) and self-efficacy (β = .281, p < .001) also exerted significant direct effects on teaching readiness, indicating that the mediation is partial rather than full. Partial mediation was confirmed for both pathways: TPACK → teaching readiness (indirect β = .180; 95% CI [.09, .27]; VAF = 36.6%) and self-efficacy → teaching readiness (indirect β = .145; 95% CI [.06, .22]; VAF = 34.0%). The model explained 52.2% of variance in reflective practice and 64.3% in teaching readiness. Practically, these findings suggest that economics teacher preparation programmes should embed structured, quality-assessed reflective activities as core, assessed components of the curriculum, alongside existing efforts to build technological-pedagogical knowledge and professional self-efficacy, rather than treating reflection as supplementary enrichment. This study provides the first empirical integration of Bandura’s self-efficacy theory, the TPACK framework, and Schön’s reflective practitioner theory in a unified mediation model tested in Indonesian pre-service economics teacher education.